Use of Metaphors by Jawaharlal Nehru - Gupta, Rakesh (2006)
Metaphors are used by and for leaders universally. For a leader to be a democratic communicator, metaphors give an insight into his intellectual and democratic credentials. Metaphors are decorative for the classicists and constitutive for romanticists and modernists. In using metaphors, Nehru borrows from various fields with telling effect to drive home his point through his writings and speeches.